Produção de antiveneno botrópico em ovos de galinha - Amanda Soriano Araujo de Souza Moreira (2007)
The aim of this work was develop an antivenom from eggs of hens immunized with Bothrops antigen and to evaluate its potency. Adults Single Comb White Leghorn hens were immunized with venom of five species of snakes of the genus Bothrops. The purification of the immunoglobulin Y (IgY) was done by ammonium sulfate 20% precipitation (w/v) and 2.69mg of pure IgY/ml of yolk was produced. The IgY from egg-yolk neutralized the toxic lethal activities of Bothrops venom. The median effective dose (ED-50) of the IgY anti-Bothrops venom was365ìL/2LD-50 and 1ml neutralized 0.154mg of venom